(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
In this study, water samples were collected from six stations in January 2013 and April 2013 with the aim of determining the water quality of Shatt Al-Arab River, physical and chemical parameters (pH, dissolved oxygen, phosphate, nitrate, calcium, magnesium, total hardness, sulphate, chloride, total dissolved solids, electrical conductivity, and alkalinity) were evaluated. The parameters were analyzed and evaluated separately according to its suitability for drinking water as recommended by World Health Organization (WHO). The mean value of electrical conductivity is about 6800 µS/cm and exceeds 2000 µS/cm recommended by WHO. The concentration of sulfates is almost above 250 mg/L (recommended by WHO) in all the stations. The result of this evaluation showed that the water quality of Shatt Al-Arab River is not suitable for drinking. The comparison of the obtained and the WHO standards were indicated before using it in agricultural purposes.